Media Edukasi Kartu Bergambar untuk Memilah Sampah pada Siswa PAUD Srikandi - Mahdalena, Vina; Handayani, Lusia; Uljanatunnisa, Uljanatunnisa (Universitas Nusantara PGRI Kediri, 2022)
Environmental communication has shifted to the concept of Sustainable Development Goals (SDGs) or Sustainability Communication. Data from the Ministry of Environment and Forestry (KLHK) in 2019, Indonesia produces at least 64 million tons of waste piles every year. Based on this data, about 60% of the waste is transported and dumped to the final dump, 10% of the waste is recycled, and the remaining 30% is not managed. In fact, the government has a target in 2025 that waste must be managed 100%. The solution that we can provide as academics in the field of Communication Science is to help teacher to educate their students what is meant by